After the degree: research psychology in the 'real world' - Rascher, Candice Lee (My University, 2016)
Research psychology is one of the five categories in which one can register as a psychologist with the Health Professions Council of South Africa (HPCSA). It is, however, the most under-represented and under-researched category of the five. Many people who are eligible to register choose not to, but presumably still obtain employment. This raises questions regarding what these people are doing and what influenced their decisions to register or not to register. The aims of this research study were thus to track former research psychology masters students and gain an understanding of the different career paths this degree led them to, and why they chose to pursue a particular path. In addition, this research aimed to determine whether or not former research psychology masters students registered with the HPCSA as a research psychologist, and their reasons for doing so or not doing so, thus enabling evaluation of the relevance of the category among those with potential eligibility to occupy it. This study also sought to evaluate the degree of transformation in this division of psychology, and provide valuable career information for students interested in studying this degree. A sample of 122 former research psychology masters students was obtained through a purposive snowballing sampling technique. The respondents completed an online survey consisting of a mixture of forced choice and open ended questions. Results showed that it does not seem to be of paramount importance to be registered as a research psychologist with the HPCSA to conduct research that is considered valuable to the community, or, more broadly, to do the kind of jobs that this degree would qualify one to do. Respondents were able to pursue a variety of different career paths despite their registration status. These career paths included working in academia, health/social research, marketing and corporate research, monitoring and evaluation and psychometrics. Results also showed that there is some evidence for the transformation of psychology, with a slightly more diverse group of students in recent years, however not enough to show significance
A research project submitted in partial fulfillment of the requirements for the degree of BA Masters (Research Psychology) in the Faculty of Humanities, University of the Witwatersrand, February/May 2016.
Keywords: Psychology--Research